Long-Term Effects of April, August, or October Prescribed Fire on Yearling Stocker Cattle Performance and Native Rangeland Plant Composition in the Kansas Flint Hills - Zachary M. Duncan; Alan J. Tajchman; Jack Lemmon; William R. Hollenbeck; Dale A. Blasi; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2024)
Objective:The objective of our experiment was to determine if prescribed fire applied in April, August, or October influenced stocker growth performance or plant community characteristics in the Kansas Flint Hills over a 6-year period. Study Description:A total of 1,939 yearling stocker cattle were assigned to one of three prescribed-burn treatments: spring (April 11 ± 5.7 days), summer (August 25 ± 6.2 days or fall (October 2 ± 9.0 days) over a 5-year period. Calves were grazed from May to August for 90 days. Individual body weights were recorded at the start and end of the grazing season. Native plant composition and soil cover were evaluated annually in June using a modified step-point method. The Bottom Line:Shifting prescribed fire from April to August or October reduced yearling stocker cattle weight gains by 10 to 14 lb during a 90-day grazing season. Ranchers are encouraged to consider the cost associated with herbicides versus the costs associated with reduced growth performance when developing a strategy for sericea lespedeza (Lespedeza cuneata) control.
Keywords: prescribed fire; stocker cattle; tallgrass prairie